1989
DOI: 10.1111/j.1476-5381.1989.tb16896.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and binding studies with muscarinic M2‐subtype selective antagonists

Abstract: 1 The potency of a series of selective muscarinic antagonists has been measured on two functional isolated tissue preparations (rat ileum and atria) and these compared with their potency on a range of binding preparations in order to determine whether the subtypes of M2 receptor measured functionally are the same as those measured in binding studies. 2 On the functional preparations pirenzepine, hexahydrosiladiphenidol (HSD) and 4-diphenylacetoxy-N-methylpiperidine (4-DAMP) were more potent on the ileum than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 30 publications
5
19
0
Order By: Relevance
“…The affinities obtained at uterine muscarinic receptors of immature guinea-pigs were compared to those determined at M 1 (rabbit vas deferens), M 2 (guinea-pig atria) and M 3 receptors (guinea-pig ileum). The antimuscarinic potencies of the antagonists at Mb M2 and M 3 receptors (pArvalues, Table 1) werein good agreement with their affinity estimates determined in radioligand binding studies (Lazareno and Roberts 1989;Waelbroeck et al 1989) and previous functional studies (Barlow et al 1976;Gilani and Cobbin 1986;Micheletti et al 1987;Eltze 1988;Eltze et al 1988;Waelbroeck et al 1989;. A comparison of these affinity values with those determined at uterine muscarinic receptors suggests that the muscarinic receptor mediating contractions of the guinea-pig uterus is pharmacologically unique ( Table 1 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The affinities obtained at uterine muscarinic receptors of immature guinea-pigs were compared to those determined at M 1 (rabbit vas deferens), M 2 (guinea-pig atria) and M 3 receptors (guinea-pig ileum). The antimuscarinic potencies of the antagonists at Mb M2 and M 3 receptors (pArvalues, Table 1) werein good agreement with their affinity estimates determined in radioligand binding studies (Lazareno and Roberts 1989;Waelbroeck et al 1989) and previous functional studies (Barlow et al 1976;Gilani and Cobbin 1986;Micheletti et al 1987;Eltze 1988;Eltze et al 1988;Waelbroeck et al 1989;. A comparison of these affinity values with those determined at uterine muscarinic receptors suggests that the muscarinic receptor mediating contractions of the guinea-pig uterus is pharmacologically unique ( Table 1 ).…”
Section: Discussionsupporting
confidence: 80%
“…M 2 and M 3 receptors are primarily found in lower brain areas and in peripheral effector argans such as heart (M 2 ), smooth muscle (M 3 ) and glands (M 3 ) and display low affinity for pirenzepine. They can be distinguished by the use of selective antagonists such as methoctramine and AF-DX 116 (M 2 > M 1 > M 3 ) (Melchiorre et al 1987;Hammer et al 1986;Micheletti et al 1987), himbacine (M 1 ~ M 2 > M 3 ) (Gilani and Cobbin 1986;Lazareno and Roberts 1989), sila-hexocyclium (M 1 ~ M 3 > M 2 ) Waelbroeck et al 1989), 4-DAMP and hexahydro-sila-difenidol (M 3 ::? :: M 1 > M 2 ) (Barlow et al 1976;Mutschier and Lambrecht 1984;.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of himbacine, AF-DX 384 and AQ-RA 741 to discriminate between functional responses at muscarinic M 1 and M 2 receptors in rabbit vas deferens contrasts with reports on the ability of the antagonists to distinguish between these receptor types in binding sturlies (Lazareno and Roberts, 1989;Doods et al, 1991;Dörje et al, 1991b). However, although pharmacological (Eltze, 1988) and immunological techniques using subtype-specific antisera (Dörje et al, 1991a) have shown that rabbit vas deferens is endowed only with M 1 and M 2 receptors, the inability of these antagonists to discriminate M 1 from M 2 receptor-mediated responses in rabbit vas deferens remains unclear and deserves further investigation.…”
Section: Agonist Studiesmentioning
confidence: 59%
“…Thus, the absolute and relative potencies of himbacine, pirenzepine and methoctramine measured against muscarinic inhibition of ICa are very similar to the ligand displacement potencies on putative M4 receptors in both NG 108-15 cells and rabbit lung (Lazareno et al, 1990), and clearly differ from their potencies at M1, M2 or M3 binding sites (Lazareno et al, 1990) or at the corresponding receptor subtypes in functional assays (e.g. Brown et al, 1980;Lazareno & Roberts, 1989). Although the potency of pirenzepine against ICa inhibition (pKB 7.74) was slightly higher than its binding potency in NG 108-15 cells (pKB 7.2;Lazareno et al, 1990), the accuracy of functional pKB calculations is probably limited by the non-parallel shift of the dose-response curve (see below).…”
Section: Discussionmentioning
confidence: 95%